2017
DOI: 10.3389/fphys.2017.00132
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Specific Capacity to Use Elastic Energy in the Patellar and Achilles Tendons of Elite Athletes

Abstract: Introduction: During running and jumping activities, elastic energy is utilized to enhance muscle mechanical output and efficiency. However, training-induced variations in tendon spring-like properties remain under-investigated. The present work extends earlier findings on sport-specific profiles of tendon stiffness and cross-sectional area to examine whether years of distinct loading patterns are reflected by tendons' ability to store and return energy.Methods:Ultrasound scans were performed to examine the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…The Achilles tendon stores and recovers strain energy to improve mechanical energy generation-absorption of the triceps surae muscles and reduce metabolic cost during dynamic activities ( Alexander and Bennet-Clark, 1977 ; Roberts et al, 1997 ; Lichtwark and Wilson, 2005 ; Wiesinger et al, 2017 ). In vivo studies have shown that Achilles tendon geometry and/or mechanical properties adapt to long-term mechanical loading in a manner that is specific to the type and duration of the applied loads ( Bohm et al, 2015 ; Wiesinger et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Achilles tendon stores and recovers strain energy to improve mechanical energy generation-absorption of the triceps surae muscles and reduce metabolic cost during dynamic activities ( Alexander and Bennet-Clark, 1977 ; Roberts et al, 1997 ; Lichtwark and Wilson, 2005 ; Wiesinger et al, 2017 ). In vivo studies have shown that Achilles tendon geometry and/or mechanical properties adapt to long-term mechanical loading in a manner that is specific to the type and duration of the applied loads ( Bohm et al, 2015 ; Wiesinger et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the exact mechanism behind the differences in fascicle behavior and EMG activity between the groups, we hypothesize that this is related to the chronic repetitive overloading experienced by the cadets 12,18,57 . We are unable to detect the location of these physiological adaptations, but it is reasonable to assume that changes in the elastic elements of the MTU (eg, altered tendon and aponeuroses stiffness) might have facilitated the more economical function of the contractile elements of the cadets' triceps surae muscles.…”
Section: Discussionmentioning
confidence: 89%
“…Although a primary scientific consensus regarding short to medium exposure (<20 weeks) to external overloading and its effects on knee and ankle musculotendinous structures has been gradually formulated, 2,5,6,9 the evidence on long‐term exposure is more variable. The studies examining adaptations to prolonged overloading (>6 months) have mainly targeted specific populations (eg, long‐distance runners) who had undergone some years of habitual overloading due to their routine physical activity 7,10‐18 . This is understandable as long‐term monitoring designs with pre‐post measurements pose considerable challenges to the researcher.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when comparing concentric and eccentric contractions, it is worth noting that the overwhelming majority of research is carried out on lower limb tendons (patellar and Achilles). This apparent bias may be due to their specific role within energy retention and power amplification during movement [31,32]. Thus, both the patellar and Achilles tendon have high functional significance and, hence, high research interest.…”
Section: Are Eccentric Contractions More Effective Than Concentric Fomentioning
confidence: 99%